Association between maternal attitude towards female circumcision and daughter's circumcision status. Issue 3 (25th June 2021) - Alemu, Dawit G.; Haile, Zelalem T.
Abstract: Objective: Female genital mutilation is a public health problem resulting in multiple health complications. In Ethiopia, female circumcision is widely practiced, with women taking center stage in the perpetuation of the practice. Using the Theory of Planned Behavior for variable selection, the following study assessed the association between maternal attitude towards female circumcision and daughter's circumcision status. Methods: From the 2016 Ethiopian Demographic and Health Survey, we analyzed a subsample of 6948 women. The outcome variable assessed daughter's circumcision status; the main independent variable assessed participant's opinion towards female circumcision. We conducted univariate, bivariate, and multiple logistic regression analyses. Results: In the bivariate analysis, none of the variables, except for religion, showed any association with daughter's circumcision status. In the multivariable regression model, several variables showed a significant association with daughter's circumcision status. Older, rural, and circumcised women were more likely to have at least one daughter circumcised, but wanting female circumcision to stop, being a Muslim, and having at least a secondary education were negatively associated with daughter's circumcision status. Conclusion: Our findings suggest that eliminating female circumcision may require changing maternal attitudes towards the practice by targeting rural, circumcised, and older women with no formal education. Abstract : Eradicating female circumcision requires changing maternal attitude towards the practice by targeting rural, circumcised, and older women with no formal education.